2005
DOI: 10.5380/avs.v10i2.4418
|View full text |Cite
|
Sign up to set email alerts
|

Preferência De Eqüinos Em Pastejo: Efeito Da Altura De Dosséis De Gramíneas Do Gênero Cynodon

Abstract: RESUMO -O experimento foi conduzido no Centro de Estações Experimentais da UniversidadeFederal do Paraná, em fevereiro de 1998, quando as gramíneas Cynodon spp. cv Tifton 85, Cynodon nlemfuensis cv Tifton 68, Cynodon spp. cv Tifton 44, Cynodon nlemfuensis (Porto Rico) e Cynodon nlemfuensis (Estrela Roxa) foram estabelecidas em parcelas em um delineamento inteiramente casualizado com parcelas subdivididas e quatro repetições. As parcelas foram subdivididas em duas alturas do dossel (alto e baixo) caracterizadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 10 publications
0
4
0
15
Order By: Relevance
“…When height and DMY are greater, LSR is smaller, but this was not observed in the 4th cut. Dittrich et al (2005) found LSRs of 1.79 and 1.75 for Tifton 85 plants that were 12 and 25 cm tall. A LSR of approximately 1.2 contains about two thirds of total DM is available in leafs.…”
Section: Resultsmentioning
confidence: 91%
“…When height and DMY are greater, LSR is smaller, but this was not observed in the 4th cut. Dittrich et al (2005) found LSRs of 1.79 and 1.75 for Tifton 85 plants that were 12 and 25 cm tall. A LSR of approximately 1.2 contains about two thirds of total DM is available in leafs.…”
Section: Resultsmentioning
confidence: 91%
“…There are characteristics that are peculiar to the equine species (Domingues, 2009), so information on nutritional quality cannot be applied without careful evaluation of how feed is consumed (Dittrich et al, 2005) or if it is effectively consumed. According to LaCasha et al (1999), when new feed types are added to the equine diet, voluntary intake should be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…While there are studies that evaluate their quality for horses, there is a need for studies that look at characteristics peculiar to horses (Domingues, 2009) and carefully evaluate voluntary feed intake of these forages under practical conditions (Dittrich et al, 2005;Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Os gêneros de leguminosas mais utilizados na alimentação de eqüinos são Trifolium, Medicago, Vicia e Lotus (Benyovszky, 1998). Entre as de clima temperado a mais preferida é Trifolium repens (trevo branco) (McCann & Hoveland, 1991;Dittrich et al, 2007) e o Lotus corniculatus (cornichão) é de baixa aceitabilidade (Dittrich et al, 2005).…”
Section: Preferência Seletividade E Velocidade Na Colheita Da Forragemunclassified
“…A composição botânica da pastagem é uma importante variável na decisão do animal para a escolha do local de pastejo. Os eqüinos preferem sítios de pastejo onde há mistura de espécies forrageiras, gramíneas e leguminosas, despendendo maior tempo de pastejo nestes sítios, do que sítios de pastejo onde as mesmas espécies encontram-se puras (Dittrich et al, 2005). A seleção da dieta é identificada pela aceitação ou rejeição de certos componentes da pastagem (plantas ou partes das plantas), sendo de grande importância para a nutrição e produtividade dos eqüinos.…”
Section: Preferência Seletividade E Velocidade Na Colheita Da Forragemunclassified